Floristic composition and structure of Eurycoma longifolia habitat in Muka Kuning Nature Tourism Park, Riau Islands, Indonesia - ARIDA SUSILOWATI; HENTI HENDALASTUTI RACHMAT; KUSUMADEWI SRI YULITA; KESUMA WIJAYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Susilowati A, Rachmat HH, Yulita KS, Wijaya K. 2023. Floristic composition and structure of Eurycoma longifolia habitat in Muka Kuning Nature Tourism Park, Riau Islands, Indonesia. Biodiversitas 24: 2836-2842. Eurycoma longifolia Jack, locally called as pasak bumi,is a popular medicinal plant which is known to have properties in curing various diseases. The root of E. longifolia is the organ that has the highest aphrodisiac content so hunting for the roots of E. longifolia destructively causes a significant population decline. Information regarding vegetation community around the habitat of this species is crucial in determining appropriate conservation actions. Muka Kuning Nature Tourism Park (TWA) located in Batam Island, Riau Islands Province is one of the natural habitats of E. longifolia, yet information regarding the state of vegetation in this area has not been obtained. This study aims to determine the floristic composition and structure of vegetation in the habitat of E. longifolia in Muka Kuning Nature Tourism Park focusing on the parameters of Important Value Index (IVI) and biodiversity indices. Vegetation analysis was applied using purposive sampling method based on the presence of E. longifolia individuals. The results showed that the IVI of E. longifolia at the growth stage of seedlings, saplings, poles and trees were 18.1%, 21.9%, 12.14% and 0%, respectively. No individual E. longifolia was found at the tree level which might be attributable to the habitus of this species which is small-sized tree or woody shrub with maximum height of 15 m. The vegetation community at the studied area had Shanon-Wienner diversity index (H') from 2.27 to 3.12 and the Evenness index from 0.88 to 0.98, which is categorized as high. The results of this study imply that the natural habitat of pasak bumi in the TWA Muka Kuning is classified as good and tighter area protection is highly recommended to protect valuable biodiversity in it including E. longifolia.